The wearproofness of materials is in the conditions of wear the semifastened abrasive with local shock loadings and jamming of parts - Антонюк, Д.А.; Редька, М.О. (Problems of Tribology, 2014)
This paper covers the results of steels and alloys tests under conditions of dispersants beats operation for crushing slag metallurgical enterprises. A mechanism of working body wear by half-fixed abrasive with local impact loads and jamming of the particles are analysed. Prototype chopper-dispersant and experimental beat for testing materials are designed and developed.